The Dark Side of Cardiac and Aortic Interventions: Unveiling Cerebral Microbleeds with Susceptibility-Weighted Imaging - Tommaso Casseri; Maria Giulia Maccaglia; Ivano Lombardo; Andrea Bianchi; Rosaria Tartarone; Giorgio Busto; Andrea Ginestroni; Sara Speziali; Walter Dorigo; Enrico Fainardi (Journal of Vascular Diseases, 2025)
Cerebral microbleeds (CMBs) are increasingly detected in patients with aortic and cardiac diseases following transcatheter aortic valve implantation (TAVI), thoracic endovascular aortic repair (TEVAR), or cardiac surgery. CMBs can be observed in magnetic resonance imaging (MRI) when susceptibility-weighted imaging (SWI) or T2*-Gradient-Echo (GRE) sequences are used. Differential diagnosis of CMBs from other causes, such as cerebral amyloid angiopathy (CAA), is crucial because of its clinical implications, particularly for anticoagulation management. A literature search was conducted using publicly available online databases to identify relevant studies for this review. The selection criteria focused on publications utilizing MRI with T2*-GRE or SWI sequences to detect CMBs in patients following cardiac or endovascular procedures. The extracted data included study characteristics, lesion distribution, and associated clinical factors. Ten studies were included in this review, with 50% analyzing a prospective cohort. Cerebral T2*-GRE or SWI hypointensities after cardiac and vascular procedures often showed a lobar distribution, thus complicating the differential diagnosis with “probable” CAA. However, CMBs seem predominantly located in subcortical white matter (SWM), unlike CAA, and commonly not associated with other alterations. Furthermore, CMBs seem to correlate with prolonged procedural duration, especially in the case of cardiopulmonary bypass, and anticoagulation therapy. Regarding etiology, various hypotheses have been proposed, with the most widely accepted being microhemorrhagic. CMBs are a common finding following cardiac procedures, either surgical or endovascular. Their distribution patterns may aid in differentiating from CAA-related lesions, with important implications for anticoagulation strategies. Identifying and characterizing these lesions is essential for optimizing postoperative management.